Multicenter Intestinal Current Measurements in Rectal Biopsies from CF and Non-CF Subjects to Monitor CFTR Function - Clancy, John P.; Szczesniak, Rhonda D.; Ashlock, Melissa A.; Ernst, Sarah E.; Fan, Lijuan; Hornick, Douglas B.; Karp, Philip H.; Khan, Umer; Lymp, James; Ostmann, Alicia J.; Rezayat, Amir; Starner, Timothy D.; et al. (PloS one, 2013)
Intestinal current measurements (ICM) from rectal biopsies are a sensitive means to detect cystic fibrosis transmembrane conductance regulator (CFTR) function, but have not been optimized for multicenter use. We piloted multicenter standard operating procedures (SOPs) to detect CFTR activity by ICM and examined key questions for use in clinical trials. SOPs for ICM using human rectal biopsies were developed across three centers and used to characterize ion transport from non-CF and CF subjects (two severe CFTR mutations). All data were centrally evaluated by a blinded interpreter. SOPs were then used across four centers to examine the effect of cold storage on CFTR currents and compare CFTR currents in biopsies from one subject studied simultaneously either at two sites (24 hours post-biopsy) or when biopsies were obtained by either forceps or suction. Rectal biopsies from 44 non-CF and 17 CF subjects were analyzed. Mean differences (µA/cm(2); 95% confidence intervals) between CF and non-CF were forskolin/IBMX=102.6(128.0 to 81.1), carbachol=96.3(118.7 to 73.9), forskolin/IBMX+carbachol=200.9(243.1 to 158.6), and bumetanide=-44.6 (-33.7 to -55.6) (P<0.005, CF vs non-CF for all parameters). Receiver Operating Characteristic curves indicated that each parameter discriminated CF from non-CF subjects (area under the curve of 0.94-0.98). CFTR dependent currents following 18-24 hours of cold storage for forskolin/IBMX, carbachol, and forskolin/IBMX+carbachol stimulation (n=17 non-CF subjects) were 44%, 47.5%, and 47.3%, respectively of those in fresh biopsies. CFTR-dependent currents from biopsies studied after cold storage at two sites simultaneously demonstrated moderate correlation (n=14 non-CF subjects, Pearson correlation coefficients 0.389, 0.484, and 0.533). Similar CFTR dependent currents were detected from fresh biopsies obtained by either forceps or suction (within-subject comparisons, n=22 biopsies from three non-CF subjects). Multicenter ICM is a feasible CFTR outcome measure that discriminates CF from non-CF ion transport, offers unique advantages over other CFTR bioassays, and warrants further development as a potential CFTR biomarker.